Balancing the equation: assessing the impact of management practices on staff and faculty wellbeing in Chinese higher education institutions - Hu, Tingting (Frontiers in Psychology, 2024)
In the realm of higher education, the interplay between work-family culture and job satisfaction, particularly among faculty and administrative staff, has emerged as a focal point of empirical inquiry, specifically in China. This paper aims to research into the relationship between these two constructs, with a specific emphasis on the mediating role of organizational justice perceptions. The rationale for this focus stems from the growing recognition of organizational justice as a critical determinant of employee attitudes and behaviors within academic institutions. This research was conducted using two distinct groups. The first group consisted of 1075 faculty members at Chinese universities, while the second group comprised 972 administrative and technical employees at these institutions. The mediational analyses provided in this study offer an enhanced comprehension of the intricate relationships under discussion. Significantly, the findings reveal that Work-Family Culture plays a crucial predictive role in influencing perceptions of Organizational Justice among both faculty and administrative staff. More importantly, the study uncovers that Work-Family Culture indirectly affects Job Satisfaction through its impact on Organizational Justice. This insight underscores the importance of harmonious work-family interactions as a determinant of job-related attitudes and satisfaction levels.